Constraints Hindering Accelerated Reduction of Stunting - Supriyono, Supriyono; Handoko, V. Rudy; Novaria, Rachmawati (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Stunting remains a significant public health issue in Jember Regency, despite the implementation of various intervention programs by national and local governments. This study aims to identify and analyze the key factors that hinder efforts to reduce stunting rates in the region. Employing a qualitative approach through in-depth interviews with local stakeholders, healthcare workers, and community members, the research reveals several major barriers, including low nutritional literacy, disparities in access to healthcare services, weak intersectoral coordination, and limited resources and supporting infrastructure. Additionally, entrenched cultural practices and inadequate parenting patterns perpetuate the intergenerational cycle of stunting, child marriage, or early marriage. The findings highlight the urgency of adopting an integrated, community-based approach and strengthening monitoring and evaluation systems to accelerate and sustain the reduction of stunting in Jember.